Assessing Upperclassmen versus Underclassmen Business Student Perceptions of Plagiarism at a Regional Institution of Higher Education - Li, Migyu; He, Feng; Lin, Shimin; Chen, Shiyng; Wang, Ziqi; Doss, Daniel (Journal of Interdisciplinary Studies in Education, 2018)
Academic dishonesty and cheating are concerns of higher education institutions. This study represents a natural extension of preceding plagiarism research that was performed at a regional institution of higher education. This study examines underclassmen versus upperclassmen perceptions of plagiarism regarding three notions:  1) necessary evil, 2) professionalism, and 3) legality.  The findings of this study confirmed the findings of its predecessors in that plagiarism was not viewed as a necessary evil, that respondents exhibited neutrality regarding plagiarism from a professional context, and that neutrality was exhibited regarding the legal perspective. One statistically significant outcome was exhibited regarding professionalism views of plagiarism.